Review of Allied Health Education: 4 - Perry, J. Warren; Mase, Darrel Jay, 1905-; Hamburg, Joseph (Book collections on Project MUSE., 2015)
This book is the fourth in a series designed to provide a current appraisal of the developments in allied health education and research, through original articles contributed by recognized leaders in the health field. The Review of Allied Health Education speaks, through enlightened commentary, to help bind the health professions into a true alliance.